1972
DOI: 10.1037/h0032972
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ingestive behaviors to taste-aversion learning in the rat.

Abstract: Rats tasting but not ingesting a flavored solution prior to toxicosis acquired weaker aversions to the flavor than subjects that actively consumed the CS during conditioning. Taste was isolated from ingestion either by curarizing the subjects or by infusing a flavored solution very rapidly into the oral cavity of non-water-deprived rats. Control groups showed that the facilitatory effect of ingestion on taste-aversion learning did not depend on the consumption of very much of the CS solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…In experiment 2, however, saccharin was presented in a bottle to deprived rats during both conditioning and testing. Stronger taste avoidance is produced when rats actively consume saccharin during conditioning than when they are passively infused with saccharin (Domjan and Wilson 1972). Therefore, it is possible that the failure of DPAT to interfere with taste avoidance when measured in a two-bottle test in experiment 2 was the result of stronger conditioning than in experiment 1.…”
Section: Discussionmentioning
confidence: 97%
“…In experiment 2, however, saccharin was presented in a bottle to deprived rats during both conditioning and testing. Stronger taste avoidance is produced when rats actively consume saccharin during conditioning than when they are passively infused with saccharin (Domjan and Wilson 1972). Therefore, it is possible that the failure of DPAT to interfere with taste avoidance when measured in a two-bottle test in experiment 2 was the result of stronger conditioning than in experiment 1.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies suggest that conditioning by IO taste exposure may produce weaker conditioning than does active consumption of the taste from a bottle (e.g., Domjan & Wilson, 1972;Fouquet et al, 2001;Wolgin & Wade, 1990;Yamamoto et al, 2002). More recently, however, Limebeer and Parker (2006) demonstrated that the strength of the expressed taste aversion was a function of the similarity of methods of CS exposure (bottle or IO) in conditioning and in testing, rather than simply the mode of fluid delivery per se.…”
Section: Discussionmentioning
confidence: 99%
“…1976; Domjan & Wilson, 1972). Somewhat surprising was the relative lack of changes in deprivation state influencing the degree of transfer, given Peck and Ader's (1974) results.…”
Section: Gillette Bellingham and Martinmentioning
confidence: 99%